Topology optimization of a rowing terminal device for an upper limb prosthesis. (November 2022) - Calcerrada, Román; Donoso, Alberto; Aranda, Ernesto; McKeown, David J.; Ramos, Francisco
Highlights: Application of TO techniques and structural analysis to a novel sport prosthesis for rowing. Reduction of weight and cost on the prosthesis while satisfying the mechanical requirements. Workow for the analysis and optimization of future sport prosthetic devices. Detailed implementation of bearing load functions to obtain more realistic FEM simulations. Workow to obtain manufacturable pieces from topology optimization software. Abstract: Prostheses are as old as humans, although current conceptions have progressed far from early designs. The prosthesis world is a field in constant evolution, either aiming to replace or to duplicate parts of the human body. In the last four decades, since the inception of activity-specific prosthesis, the industry of sport prosthetic devices has developed considerably and with an increasing number of sport specific systems available. However, due to the complexity and uniqueness of applications, extensive issues remain unresolved. This work presents a new body-powered sport prosthetic mechanism that allows a person with an unilateral upper limb disability to row. A complete computational analysis of the mechanical properties of the device has been performed using finite element methods. Following this, topology optimization methods were applied to obtain a substantial reduction in device weight while retaining the necessary mechanical strength. This process shows the potential of topology optimization in the design of prosthetic terminal devices, achieving lighter and, hence, cheaper and more competitive mechanisms.